Effects of Mobile Money Transfer Operational Costs on Profitability of Medium and Small Enterprises in Oyugis Township, Homabay County, Kenya - Otilah, Gerishon Obalah; Nyagol, Michael; Koech, Caroline Sitienei (International Journal of Social Science and Economic Research, 2019)
Micro and Small Enterprises (MSE) are considered a vital engine in national growth it terms of employment and national income. As noted by Arianoff, (2010), MSEs is a source of employment as well as an instrument for poverty reduction within our communities. This study focused to establish effect of Mobile Money Transfer (MMT) services on profitability of MSEs operating in Oyugis Town of Homabay County, Kenya.. In its attempt to establish the effect of MMT operational cost on profitability of MSEs in Oyugis Town the study adopted Technology Acceptance Model (TAM). Data was obtained using questionnaires from MSEs owners. From target population of 133 a sample of 52 MSEs owners provided information through a structured questionnaire which was analyzed using descriptive and inferential statistics aided by Statistical Package for Social Science (SPSS). The findings of the study revealed that MMT operational cost had positive and significant effect on profitability of MSEs in Oyugis Town. Operational cost reduction of mobile money transfer services has a significant effect on profitability (β= .219; p<.05).The study recommended that MSE should adopt mobile money transfer in managing transactions, administrative management, managing credit and overheads. Secondly, it will create easy access credit, transferring payments to increase efficiency in working customers and suppliers, better staff utilization will lead to reduced operational cost and increased convenience and maintaining liquidity value of cash within virtual network. On further research, the study recommended the need to look on the effect of adoption of MMT on sustainability of MSEs.
Keywords: Mobile Money Transfer; Operational Costs; Medium and Small Enterprises